Beyond governance: the need to improve the regulation of international sport - Chappelet, J.-L. (Sport in Society: Cultures, Commerce, Media, Politics, 2018)
Governance has been a prominent word in international sport circles since the beginning of the twenty-first century. However, better governance will not cure all the ills of this wide-ranging sector and its numerous governing bodies, many of which, including the International Olympic Committee (IOC), the Fédération Internationale de Football Association (FIFA) and the International Association of Athletics Federations (IAAF), have been shaken by corruption. This paper discusses the need for a new approach to sports governance that combines aspects of both corporate and democratic governance. It also shows that combating problems such as doping, match-fixing, hooliganism and sport corruption requires a wider international legal framework, developed through cooperation between government authorities and the sports sector. Only international regulation will ensure sport gains the improved governance it needs in order to preserve its integrity and value in the eyes of the public.